Pelaksanaan Jaminan Sosial Bagi Korban Kecelakaan Lalu Lintas Jalan Pada Pt. Jasa Raharja Cabang Bali Wilayah Gianyar - I Wayan Parandika; I Nyoman Putu Budiartha; Ni Made Puspa Sutari Ujianti (Jurnal Preferensi Hukum, 2021)
The development of technology evolves every year. This affects the economic aspects of transportation services. It cannot be denied that every means of transportation has risks in its journey. In this case, there must be implementation in social security for accident victims. The purpose of this research is to reveal the implementation of social security for victims of traffic accidents as well as the obstacle factors in the implementation of road social security at PT. Raharja Bali Gianyar Region services for road traffic accident victims. The method used is empirical legal research with a conceptual and a case approach. Sources of legal materials used are secondary, primary and tertiary sources of law and then analyzed descriptively. The data collection technique was carried out by interviewing the victim and the victim's heirs. The result of this research is the implementation of social security for road traffic accident victims at PT. Jasa Raharja Bali, Gianyar Region is carried out in accordance with the applicable laws and regulations. Factors that hinder its implementation include: the community does not know the scope of the guarantees that are covered, the external obstacles, namely correspondence and administrative management, and obstacles from the side of accident victims who submit claims to receive compensation from PT Jasa Raharja, Bali, Gianyar Region namely, obstacles in determining heirs for accident victims who died existed in processing a Police Report which required sufficient witnesses